The role of the Syrian curriculum in the development of democvatic values- Astudy of a content analysis of the notional education book for the decond Grade (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed at identifying the democratic values ​​in the second grade secondary education in the Syrian Arab Republic, identifying the places in which the democratic values ​​were included within the study units, as well as identifying the appeals that the students address to the students. The research community was all the paragraphs, images and documents that dealt with democracy and its values ​​in the book of national education for the second grade secondary, the number of 145 analytical articles. The study found that the curricula of the Ministry of Modern Education in the Syrian Arab Republic are valuable in their content and the method of presenting them to the issues in general. And the book of national education for the second grade secondary, contains many values ​​such as tolerance, justice, equality, human rights and other issues and democratic values ​​contained in the lessons and activities and attachments, and methods of persuasion were rational and distinct.